2017
DOI: 10.1155/2017/5718125
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profile of Fat of Grass Carp, Bighead Carp, Siberian Sturgeon, and Wels Catfish

Abstract: The objective of this study was to determine fish species differences in fatty acid profile of the fat of farmed grass carp, bighead carp, Siberian sturgeon, and wels catfish so as to compare the consumer health benefits they provide. Fatty acid composition range was as follows: saturated fatty acids (SFA), 16.32%–32.96%; monounsaturated fatty acids (MUFA), 41.84%–55.31%; and polyunsaturated fatty acids (PUFA), 13.4%–26.31%. The total content of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
(52 reference statements)
2
1
0
Order By: Relevance
“…Carp and trout are medium-fat fish, their fat content is between 2-10% according to the farming and feeding conditions (27). Our results correspond with the results published by Pyz-Aukasik and Kowalczyk-Peczka (28). These authors reported Time -the day of the year (1st January -day 1); SD -standard deviation…”
Section: Main Nutrients Analysessupporting
confidence: 93%
“…Carp and trout are medium-fat fish, their fat content is between 2-10% according to the farming and feeding conditions (27). Our results correspond with the results published by Pyz-Aukasik and Kowalczyk-Peczka (28). These authors reported Time -the day of the year (1st January -day 1); SD -standard deviation…”
Section: Main Nutrients Analysessupporting
confidence: 93%
“…Huang et al studied the hybrid sturgeons of Amur sturgeon Acipenser schrenckii and Huso dauricus and found that palmitic acid (C16:0, 18.89–21.02%) was the main SFA in all parts; oleic acid (C18:1, 31.81–34.08%) was the main MUFA; and in PUFA, the content of linoleic acid (C18:2, 17.72–22.34%) was the highest, followed by DHA (C22:6, 4.56–6.14%) and EPA (C20:5, 3.13–3.57%) ( 15 ). The contents of palmitic acid, oleic acid, linoleic acid, DHA, and EPA in Siberian sturgeon reported by Nieminen ( 26 ) and Pyz Lukasik ( 27 ) are also similar to those reported by Huang and Chen.…”
Section: Nutritional Components and Biological Activities Of Sturgeon...supporting
confidence: 81%
“…Although it is not the top‐produced finfish species in the world, for example, compared with grass carp ( Ctenopharyngodon idella ), Atlantic salmon provides a substantial quantity of the omega‐3 (n‐3) long‐chain polyunsaturated fatty acids (LC‐PUFAs), specifically eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), for human consumers. For example, a 100 g serving of farmed Atlantic salmon fillet contains approximately 1 g of EPA plus DHA, 2 compared to approximately 0.06 g in grass carp, and other top‐produced finfish species, such as 0.5 g in bighead carp ( Hypophthalmichthys nobilis ), 3 0.08 g in Nile tilapia ( Oreochromis niloticus ) and 0.2 g in common carp ( Cyprinus carpio ) 4 . The dietary recommended intake of EPA and DHA for humans is between 0.2 and 0.5 g/day for an adult, to lower the risk of cardiovascular and inflammatory disease, 5 and is higher for pregnant/lactating people due to their critical importance in fetus and infant brain development 6–8 .…”
Section: Introductionmentioning
confidence: 99%